The role of Candida albicans SPT20 in filamentation, biofilm formation and pathogenesis. - Xiaojiang Tan (Public Library of Science (PLoS), 2014)
Candida albicans is a ubiquitous fungus, which can cause very serious and sometimes life-threatening infections in susceptible patients. We used Caenorhabditis elegans as a model host to screen a library of C. albicans mutants for decreased virulence and identified SPT20 as important for virulence. The transcription co-activator SPT20 was identified originally as a suppressor of Ty and solo δ insertion mutations, which can cause transcription defects in Saccharomyces cerevisiae. It is resistant to the toxicity caused by overexpression of GAL4-VP16. We constructed a C. albicans spt20Δ/Δ mutant and found the spt20Δ/Δ strain was significantly less virulent than the wild-type strain SC5314 in C. elegans (p < 0.0001), Galleria mellonella (p < 0.01) and mice (p < 0.001). Morphologically, spt20Δ/Δ mutant cells demonstrated a "snow-flake" shape and clustered together; prolonged culture times resulted in increased size of the cluster. The clustered morphology was associated with defects in nuclei distribution, as the nuclei were not observed in many cellular compartments. In addition, the C. albicans spt20Δ/Δ mutant resulted in defects in hyphae and biofilm formation (compared to the wild-type strain, p < 0.05), and sensitivity to cell wall and osmotic stressors, and to antifungal agents. Thus our study demonstrated a role of C. albicans SPT20 in overall morphology and distribution of nuclear material, which may cause the defects in filamentation and biofilm formation directly when this gene is deleted.